Efficacy of pulse intravenous methylprednisolone in epileptic encephalopathy: a randomised controlled trial. Issue 12 (1st September 2022) - Rangarajan, Anush; Mundlamuri, Ravindranadh Chowdary; Kenchaiah, Raghavendra; Prathyusha, Parthipulli Vasuki; Viswanathan, Lakshminarayanapuram Gopal; Asranna, Ajay; Chatterjee, Aparajita; Nagappa, Madhu; Seshagiri, Doniparthi Venkata; Kulanthaivelu, Karthik; Bharath, Rose Dawn; Jitender, Saini; et al.
Abstract : Background: High-level evidence for using steroids in epileptic encephalopathy (EE), other than West syndrome (WS), is lacking. This study investigated the efficacy and safety of pulse intravenous methylprednisolone (IVMP) in EE other than WS. Methods: This is an open-label evaluator-blinded randomised controlled study. Children aged 6 months or more with EE other than WS were included. Eighty children were randomised into intervention and non-intervention groups with 40 in each group. At the first visit (T1) seizure frequency, electroencephalographic (EEG) and Vineland Social Maturity Scale (VSMS) were obtained, and antiseizure medication (ASM) were optimised. After 1 month (T2), subjects were randomised to intervention (ASM+3 months IVMP pulse) or non-intervention group (only ASM) with 40 subjects in each group. They were followed up for 4 months (T3) and assessed. Results: After 4 months of follow-up, 75% of patients receiving IVMP had >50% seizure reduction versus 15.4% in control group (χ2=28.29, p<0.001) (RR 4.88, 95% CI 2.29 to 10.40), median percentage change in seizure frequency (91.41% vs 10%, p<0.001), improvement in EEG (45.5% vs 9.4%, χ2=10.866, p=0.001) and social age domain of VSMS scores (Z=−3.62, p<0.001) compared with baseline. None of the patients in the intervention group had any serious side-effects. Discussion: Three- month pulse IVMP therapy showed significant improvement in seizure frequency, EEG parameters and VSMS scores, with no steroid-related serious adverse effects. It can be considered as a safe and effective add on treatment in children with EE other than WS. Trial registration number: CTRI/2019/02/017807.